Pengaruh Perbedaan Suhu Kalsinasi terhadap Band Gap dan Konduktivitas Listrik Lapisan Tipis CuSnO3 - Syafrian, Syafrian; Sanjaya, Hary (Lembaga Yasin AlSys, 2024)
The main semiconductor materials used are the elements Ge (germanium) and Si (silicon). The element Ge is found in nature in small quantities and silicon is the most abundant element in the earth's crust but its conductivity is low. The semiconductor material that has recently been frequently researched is Copper Tin Oxide (CuSnO3). CuSnO3 has high electrical conductivity and is quite abundant on the earth's surface. The synthesized CuSnO3 semiconductor is applied as a thin layer because of several advantages such as large output voltage, small electrode mass, and also a fairly long service life. This research aims to determine the optical and electrical properties of CuSnO3 thin films synthesized using the sol-gel method with dip coating techniques. CuCl2·2H2O, SnCl2·2H2O, methanol, and monoethanolamine (MEA) are the precursors used. The synthesized CuSnO3 thin layer was characterized using a UV-DRS instrument to determine the band gap value and tested using the four point probe method to determine its electrical conductivity. The band gap values with calcination temperatures of 500°C, 550°C, and 600°C are 2.55 eV, 2.83 eV, and 2.95 eV, respectively, with electrical conductivity of 348.46 102 S/cm, 155.48 102 S/cm, and 107.63 102 S/cm. From these data it can be concluded that the band gap value of the CuSnO3 thin layer will increase when the calcination temperature used is higher, and the conductivity decreases as the band gap value of the CuSnO3 thin film increases.